2020
DOI: 10.1016/j.amsu.2020.09.049
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 pandemic: Economic burden on patients with musculoskeletal injuries in a tertiary care hospital of LMIC; retrospective cross sectional study

Abstract: Covid-19 has adversely impacted the health care organizations by over burdening with Covid patients and suspending the elective surgeries and clinics. Hospitalization during pandemic may increase health cost of patients for elective and emergency procedure due to extra cost of covid testing and isolation. A single center retrospective study was conducted to quantify losses due to postponement of elective surgeries and extra cost for procurement of PPEs. The secondary objective was to see the effect of Covid −1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 8 publications
(7 reference statements)
2
34
0
1
Order By: Relevance
“…In one of Turkish hospitals, the total number of fractures recorded during the COVID-19 pandemic was by 61.6% lower than the number of fractures recorded in 2019 [20].Our retrospective study showed reduced numbers of pediatric (by 3.8%) and adult patients (by 22%) referred to emergency departments due to DRFs during the COVID-19 pandemic. Similar, or even more pronounced decreases over the COVID-19 pandemic period (compared to period prior to the COVID-19 pandemic ) have been reported in other countries (19-69%) [13,[15][16][17][18][19][20][21][22]24].…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…In one of Turkish hospitals, the total number of fractures recorded during the COVID-19 pandemic was by 61.6% lower than the number of fractures recorded in 2019 [20].Our retrospective study showed reduced numbers of pediatric (by 3.8%) and adult patients (by 22%) referred to emergency departments due to DRFs during the COVID-19 pandemic. Similar, or even more pronounced decreases over the COVID-19 pandemic period (compared to period prior to the COVID-19 pandemic ) have been reported in other countries (19-69%) [13,[15][16][17][18][19][20][21][22]24].…”
Section: Discussionsupporting
confidence: 61%
“…Distal radius fractures constitute a social problem [1][2][3][4][5][6][7][8][9][10][11][12][13]. The COVID-19 pandemic has had a considerable impact on the lives of both adults and children around the world [13][14][15][16][17][18][19][20][21][22][23][24]. Some schools have been closed, causing children to stay at home, and some adults work from home.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations